Competition and cooperation between brands in a segment: an analysis based on a semi-Markov model. Issue 1 (12th December 2008) - Du, Rong; Ai, Shizhong; Hu, Qiying
Because the market position of a product brand is influenced by consumers' buying behaviour, it is important to identify the potential for competition and cooperation between different brands in a product category by using consumer behaviour analysis. To help marketing managers discover the market positions of their brands and to make decisions about competitive or cooperative strategies, we propose an integrated semi-Markov model for consumer behaviour, which combines brand choice, purchase quantity and purchase timing. Based on the model, we mathematically formulate some measures for consumer behaviour and describe a brand's market structure in a new way using semi-Markov processes. The brand's market in the presented structure is classified into one transient segment and several recurrent segments, which can be further classified into loyal segments and switching segments. With the help of this brand's market structure, we analyse the coexistence of competition and cooperation among different brands. To validate the model, we conducted an experiment using the data from a consumer panel of college students.